Yerma. Past and present of the experience of female infertility - Cuervo Pollán, Ana (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2024)
This article will reflect on infertility. First of all, we will take as a starting point Yerma, a dramatic piece in which the infertility of the protagonist is masterfully dissected by its author, Federico García Lorca. Through it, the social, personal and emotional consequences that infertility has for women will be pointed out. Likewise, the implications of infertility for men will be addressed. Secondly, it will be discussed whether infertility in itself is a pathology or a state of the person that, if it were not for the significant burden it carries, would be irrelevant in terms of health and emotional well-being. And, thirdly, it will be debated whether Assisted Reproduction Techniques have solved a need or have created one: whether they have normalized the pressure to achieve motherhood or fatherhood by subjecting people, especially women, to unnecessary treatment in that it does not improve their state of health. Likewise it will be shown that the supply of assisted reproduction techniques is directly conditioned by the patriarchal and neoliberal system. Consequently, it will be emphasized that the considerations on these techniques do not exclusively concern the medical field, but must address social, political and ethical issues.